2019
DOI: 10.1111/apha.13264
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate and GABA neurotransmission are increased in paraventricular nucleus of hypothalamus in rats induced to 6‐OHDA parkinsonism: Involvement of nNOS

Abstract: Aim: Parkinson's disease (PD) is a progressive neurodegenerative disease that manifests itself clinically after reaching an advanced pathological stage. Besides motor signals, PD patients present cardiovascular and autonomic alterations.Recent data showed that rats induced to Parkinsonism by 6-hydroxydopamine (6-OHDA) administration in the substantia nigra pars compacta (SNpc) showed lower mean arterial pressure (MAP) and heart rate (HR), as reduction in sympathetic modulation. The paraventricular nucleus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…It is known that the PVN is a critical integrated center in control sympathetic outflow [ 33 ]. The receptors of γ-aminobutyric acid (GABA) in the PVN is involved in inhibiting in sympathetic outflow and blood pressure [ 34 , 35 ]. Thus, we further investigated whether GABA receptors in the PVN might mediate the effects of salusin-β in sympathetic inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the PVN is a critical integrated center in control sympathetic outflow [ 33 ]. The receptors of γ-aminobutyric acid (GABA) in the PVN is involved in inhibiting in sympathetic outflow and blood pressure [ 34 , 35 ]. Thus, we further investigated whether GABA receptors in the PVN might mediate the effects of salusin-β in sympathetic inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the central control of the cardiovascular system, it was observed that nNOS is increased in the paraventricular nucleus of the hypothalamus, an area of cardiovascular control, leading to an increase in GABAergic tone on cardiovascular function and contributing to the lower basal BP values in male 6-OHDA injured rats ( Turossi Amorim et al, 2019 ). By this way, the decreased baseline blood pressure in animals with Parkinsonism by 6-OHDA may be due to a central effect mediated by the NO in the PVN.…”
Section: Nitric Oxide In Cardiovascular Dysfunction In Parkinson's Di...mentioning
confidence: 99%
“…The boxes in red are questions and possible hypotheses. The central illustrations were taken from the cited articles by Ariza et al, 2015b and Turossi Amorim et al, 2019 . The lateral illustrations were taken from BioRender.…”
Section: Nitric Oxide In Cardiovascular Dysfunction In Parkinson's Di...mentioning
confidence: 99%
“…Investigating the mechanisms of blood pressure regulation was again a focus of a number of articles published in Acta physiologica in the recent year. The research on basic physiological questions and mechanism in model organisms is complemented with studies that include clinical patient data …”
mentioning
confidence: 99%